Avaliação sistemática do efeito de matriz em ensaios bioanalíticos por LC-MS/MS para a análise de rifampicina em fluidos biológicos - Iceri, Taciane Mitsuko (2011)
Bioanalytical assays by LC-MS/MS were conducted in order to investigate the matrix effect (ME) in the analysis of rifampicin (RIF) in biological matrices, human plasma or microsomal fractions, which were submitted to different sample pretreatment procedures: 1) off-line – solid phase extraction (SPE), protein precipitation using acetonitrila (PP(ACN)) or methanol (PP(MeOH)) and 2) on-line – by using of a restricted access media (RAM) bovine serum albumin (BSA) octyl column in a single or multidimensional mode of analysis. The ME was also determined through the employment of different chromatographic conditions and different mechanisms of ionization. Conventional stationary phases (C18 Nucleosil homemade; 5 μm, 100 Å) and columns with Fused Core technology (C18 Supelco Ascentis® Express; 2,7 μm, 90 Å), as well as, atmospheric pressure chemical ionization (APCI) and electrospray (ESI) were investigated in this work. Among the off-line sample clean-up (RIF 50 g/mL) procedures evaluated in the quantitative ME experiments by LC-ESI-MS/MS, it was found that SPE showed to be more efficient in the reduction of ME. Additionally, the chromatographic conditions using the Ascentis Express column provided the best result for ME reduction. Therefore, the Ascentis Express column was chosen to be used in the evaluation of the ionization mechanisms in either quantitative or qualitative experiments using off-line extraction configuration and, in all results obtained, the ESI ionization was less susceptible to ME than APCI. The assays of biological samples spiked before and after the off-line clean-up procedures also provided results for recovery (RE) and process efficiency (PE). For the sample preparation using the on-line RAM-C8-BSA column (5,0 x 0,46 cm I.D.; 10 m, 100 Å) two methods were developed: 1) single mode and 2) multidimensional configuration of analysis, with the C18 Ascentis Express in the second chromatographic dimension. In these procedures the ESI ionization was the ionization source employed. The ME was measured for RIF (500 ng/mL) and when the microsomal fractions was the biological fluid, the multidimensional configuration allowed a reduction of ME from 47.86 % to 14.63 % by comparing to the single mode result. For the human plasma was not possible to obtain a ME profile since this Abstract / xxvi comparison was hampered by the unidimensional data (RSD = 38.73 %). In most cases, when the results obtained from microsomal fractions and human plasma were compared, there was no predominant ME correlation between both matrices for all extraction procedures off-line and on-line. In this work, the rifampicin LC-MS/MS analysis was performed in positive ion mode, monitoring the m/z 823  791 transition.